Globalisasi dan Dakwah Muhammadiyah: Analisis Transformasi Gerakan Sosial-Keagamaan Abad ke-21 - Haq, Ihsan Abdul (Hadara : Journal of Da'wah and Islamic Civilization, 2025)
This research is important to understand how Muhammadiyah, as one of the largest Islamic organizations in Indonesia, transforms its da'wah strategy in facing the challenges and opportunities of globalization. The purpose of this study is to analyze the dynamics of Muhammadiyah's da'wah transformation as a socio-religious movement and its implications for the role of Islam and nationality in the global era. Using a qualitative-descriptive approach with literature study methods and critical discourse analysis of official documents, da'wah media, as well as organizational policies, this study found that Muhammadiyah has adopted a digitalization approach to da'wah, strengthening global issues such as social and ecological justice, and developing international networks. These results show that Muhammadiyah's da'wah has not only undergone technical changes, but also ideological transformation towards a progressive Islam that is globally relevant. The novelty of the research lies in the integrative mapping between globalization and local value-based da'wah strategies. The implications of these findings can be an important consideration in the formulation of national da'wah policies that are responsive to global dynamics and able to strengthen the position of Indonesian Islam in the international arena.